Formulation And Evaluation of Niacinamide Nanoemulgel for Enhanced Topical Delivery - D. Pawar, Rajeshwari; V. Shinde, Jitendra; Bhosale, Ashok (Journal of Neonatal Surgery, 2025)
Objective: The objective of this study was to develop and evaluate a nanoemulgel-based transdermal drug delivery system (TDDS) to enhance the skin permeability and bioavailability of niacinamide (a BCS Class III drug with high solubility and low permeability) for the treatment of pellagra, a disease caused by vitamin B3 deficiency. The formulation aimed to overcome the limitations of poor skin permeability and first-pass metabolism associated with conventional delivery. Method: Niacinamide-loaded nanoemulgels (NEG) were formulated using an oil-in-water nanoemulsion incorporated into a gel base. Various batches were prepared and evaluated for physicochemical parameters including particle size, zeta potential, drug release, entrapment efficiency, spreadability, and in vitro skin permeability. The optimized formulation was identified based on performance metrics and subjected to further evaluation for toxicity and irritation. Results: The optimized batch (F2) exhibited a particle size of 85 ± 0.14 nm and a zeta potential of –25.1564 mV, indicating stability of the formulation. In vitro drug release reached 95.7 ± 0.38% over 24 hours. The nanoemulgel demonstrated high entrapment efficiency (92.40 ± 0.007%), excellent spreadability (16.69 ± 0.035%), and favorable flow properties. In vitro skin diffusion studies showed a permeability of 98.1 ± 0.26% for batch NEG2. The formulation was found to be non-toxic and non-irritant upon evaluation. Conclusion: The niacinamide-loaded nanoemulgel formulation represents a novel, stable, and effective approach for enhancing transdermal drug delivery. It significantly improves skin permeability, drug release, and bioavailability while minimizing first-pass metabolism and adverse effects, making it a promising strategy for the topical treatment of pellagra.